Online Self-Regulated Learning and Cognitive Flexibility through the Eyes of English-Major Students - Dağgöl Gökçe Dişlen (Acta Educationis Generalis, 2023)
Introduction: Assuming responsibility of learning and showing flexibility in case of changes and problems in learning could make this process more conscious and fruitful. This is significant, particularly at a time when traditional universities are increasingly moving into online education. To address the gaps in previous self-regulated learning and cognitive flexibility research, the current study examined the students’ perceived online self-regulated learning and cognitive flexibility, and looked into the probable relationship between them.